the impact of promotional activities on decisions related to mobile purchases - dewi, lati sari (Journal of Management Review, 2025)
The research objectives at Gema Store Cellular Graphic Ciawi were to investigate: 1) The impact of promotions conducted by Gema Cellular Graphic Ciawi; 2) Purchase decisions at Gema Cellular Graphic Ciawi; 3) The effect of promotions on purchasing decisions at Gema Cellular Graphic Ciawi. The research employed a descriptive method, utilizing both primary and secondary data. Simple regression was the chosen analysis tool. The findings indicate that: 1) Promotions at Gema Graphic Cellular Ciawi Stores have a positive impact; 2) Purchase decisions at Gema Graphic Cellular Ciawi Store are favorable; 3) The influence of promotions on purchase decisions at Gema Graphic Cellular Ciawi Stores is quite strong; 4) The hypothesis test results show a significance level of 5%, confirming that promotion significantly affects purchasing decisions at Gema Graphics Cellular. The coefficient value for Promotion Determination on Purchasing Decisions is 28.8%, with the remaining 71.2% influenced by unexplored factors. Keywords: Promotion, Purchase Decision.